Women Phenomenologists Past and Present The Human Being in the World: Subjectivism and Modalities of the Real and Art - Smith, Jadwiga S.; Smith, William S.; Sassine, Marie Antonios (Analecta Husserliana, The Yearbook of Phenomenological Research, 2025)
XII, 352 p.